Substance requirements in the international taxation of intangible capital – a double edged sword? - Aparna Mathur; Kartikeya Singh; Cody Kallen (American Enterprise Institute (AEI), 2019)
The OECDs Base Erosion and Profit Shifting project has focused on income attributed to intangibles with an objective of curtailing perceived artificial profit shifting by multinational firms.
Keywords: A; 330; BEPS; economic substance; intangibles; international tax; transfer pricing; U.S. tax reform